Ekspektasi Gamers Terhadap Nilai Profesionalisme Karakter Pustakawan dalam Game Genshin Impact - Ananda Puspita Dewi; Roro Isyawati Permata Ganggi (Universitas Islam Negeri Salatiga, 2025)
The background of this research is the changing role of librarians because information needs are easily met in a digital world. This causes librarians to lose their primary identity and professional values. But one of the video games in the genre of adventure, fantasy, and RPG, Genshin Impact, has a library character in it. The problem with this study is to find out how expectations Babufess! members regarding the value of library character professionalism in the content of the game Genshin Impact. The aim of this research is to know the expectations of Babufess! members concerning the professionalism of the character of the library in the contents of Genshin Impact games when compared to the libraries in the real world. The research method used in this research is a qualitative research method with a phenomenological approach. Data collection techniques include observations, document studies, and in-depth interviews. Determination of informants using purposive sampling techniques with seven informants integrated into the Babufess! community. The results of this study showed that the library characters in the Genshin Impact game can be identified as librarians when viewed by their appearance; librarian characters are reliable and skillful in performing their work especially in the search for information; libraries are communicative and responsive when the publisher asks for help in searching information; library character can be polite when the librarian also values the character of a librarian; and then librarian character can show his empathy when he sees libraries having difficulty in finding information. The library characters in the game Genshin Impact are also capable of displaying various roles of the library profession that are not highlighted by the general public.